Label-free leukocyte sorting and impedance-based profiling for diabetes testing - Petchakup, Chayakorn (2020)
Circulating leukocytes comprise of approximately 1% of all blood cells and efficient enrichment of these cells from whole blood is critical for understanding cellular heterogeneity and biological significance in health and diseases. In this work, we report a novel microfluidic strategy for rapid (< 1 h) label-free leukocyte sorting and impedance-based profiling to determine cell activation in type 2 diabetes mellitus (T2DM) using whole blood. Leukocytes were first size-fractionated into different subtypes (neutrophils, monocytes, lymphocytes) using an inertial spiral sorter prior to single-cell impedance measurement in a microfluidic device with coplanar electrode design. Significant changes in membrane dielectric properties (size and opacity) were detected between healthy and activated leukocytes (TNF-α/LPS stimulated), during monocyte differentiation and among different monocyte subsets (classical, intermediate, non-classical). As proof-of-concept for diabetes testing, neutrophil/monocyte dielectric properties in T2DM subjects (n = 8) were quantified which were associated with cardiovascular risk factors including lipid levels, C-reactive protein (CRP) and vascular functions (LnRHI) (P < 0.05) were observed. Overall, these results clearly showed that T2DM subjects have pro-inflammatory leukocyte phenotypes and suggest leukocyte impedance signature as a novel surrogate biomarker for inflammation.